Hubungan Patron-Klien Di Lingkungan Perkebunan Tembakau Vortenlanden Klaten Jawa Tengah: Perspektif Sosiologis tentang Ketahanan Nasional. Patron-Client Relationship in Vorstenlanden Klaten Jawa Tengah: Perspektif Sosiol - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACTThis research tries to examine and describe the patron-client relationship in the society around Vorstenlanden tobacco plantation in Klaten regency, Central Java. The main issues are examined here as follow: 1) the mode of patron-client relationship since the Dutch colonization until nowdays